THE ROLE OF HE4 PROTEIN EXPRESSION IN RELATION TO CLINICOPATHOLOGICAL FEATURES OF RENAL CELL TUMORS - Jevtić, Jovan (Medical Research, 2024)
Introduction: Widespread routine ultrasound diagnostics enable early detection of kidney tumors. However, due to nonspecific symptomatology and signs that usually appear as the disease progresses, there are still patients whose diagnosis is made only in advanced stages of the disease.Aim: Our aim was to investigate the correlation of human epididymis protein 4 (HE4) expression, including the intensity and localization of HE4 positivity, with the clinical and pathohistological characteristics of kidney tumors.Material and Methods: The study included 96 kidney tumors diagnosed between 2010 and 2013 at the Institute for Pathology in Belgrade. Anti-HE4 antibodies were used for immunohistochemical analysis. Demographic, clinical, and pathohistological characteristics were examined in relation to HE4 expression.Results: No correlation was observed between HE4 expression in kidney tumors with the gender of patients and the nuclear grade of tumors. However, HE4 expression was significantly more frequent in larger tumors, specifically in tumors at stages T3 and T4, compared to tumors at stages T1 and T2 (p=0.009; p=0.006, respectively). No correlation was observed between HE4 expression and the pathohistological type of kidney tumors, but it's important to highlight that membrane expression of HE4, unlike most renal cell carcinomas, was not observed in oncocytomas.Conclusion: It’s possible that HE4 plays a role in the progression of kidney tumor growth. Membrane expression of HE4 could be used as a new parameter in differentiating renal cell carcinomas from oncocytomas.
Keywords: renal cell carcinoma, oncocytoma, human epididymis protein 4, HE4, pathohistological characteristics.